Stealing Parker - Kenneally, Miranda (Sourcebooks Fire, 2012)
Parker Shelton pretty much has the perfect life. She's on her way to becoming valedictorian at Hundred Oaks High, she's made the all-star softball team, and she has plenty of friends. Then her mother's scandal rocks their small town and suddenly no one will talk to her. Now Parker wants a new life.